2012
DOI: 10.1093/bja/aes138
|View full text |Cite
|
Sign up to set email alerts
|

Supplemental intravenous crystalloids for the prevention of postoperative nausea and vomiting: quantitative review

Abstract: Hypovolaemia after overnight fasting is believed to exacerbate postoperative nausea and vomiting (PONV). However, data on the efficacy of supplemental i.v. crystalloids for PONV prophylaxis are conflicting. We performed a literature search using CENTRAL, MEDLINE, EMBASE, CINAHL, and Web of Science. We included prospective randomized controlled trials that reported PONV event rates in patients receiving supplemental i.v. crystalloids or a conservative fluid regimen after elective surgery under general anaesthes… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

4
49
0
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 74 publications
(54 citation statements)
references
References 61 publications
4
49
0
1
Order By: Relevance
“…Blood is directed away from the gastrointestinal tract, which is an early trouble-spot for ischemia. A review by Apfel et al [5] showed that the administration of as little as 2 mL kg -1 h -1 of crystalloid fluid during surgery was associated with a higher incidence of nausea, which may be due to this type of re-distribution. An additional infusion of crystalloid fluid alleviated the problem, thereby supporting local hypovolemia as the cause.…”
Section: Role Of Fluidmentioning
confidence: 99%
“…Blood is directed away from the gastrointestinal tract, which is an early trouble-spot for ischemia. A review by Apfel et al [5] showed that the administration of as little as 2 mL kg -1 h -1 of crystalloid fluid during surgery was associated with a higher incidence of nausea, which may be due to this type of re-distribution. An additional infusion of crystalloid fluid alleviated the problem, thereby supporting local hypovolemia as the cause.…”
Section: Role Of Fluidmentioning
confidence: 99%
“…9 Among Non-pharmacological methods, besides transcutaneous acupoint electrical stimulation (TAES), acupuncture and acupressure, peri-operative liberal intravenous fluid administration has been shown to reduce PONV. 9,10,11 This study is designed to evaluate the effect of intraoperative intravenous crystalloid infusion at two different doses (30 mL/Kg and 15 mL/Kg) on the incidence of PONV, on patients undergoing diagnostic gynaecological laparoscopic surgery.…”
Section: B a C K G R O U N Dmentioning
confidence: 99%
“…However, within this particular patient group, generalisability is limited. A quantitative review of low-powered studies found that supplemental intravenous crystalloids were associated with reduced incidence of several postoperative nausea and vomiting (PONV) outcomes 41. Negating hypovolaemia from overnight fasting by administering overnight intravenous fluid infusion may be supposed to improve PONV outcomes.…”
Section: Overnight Intravenous Fluidsmentioning
confidence: 99%